Job Satisfaction Mediates Relationship Between Organizational Commitments And Employee Performance - Wagiman S., Wagiman; Sutanto, Himawan Arif (Jurnal Manajemen Dayasaing, 2019)
The research was aimed to examine the influence of organizational commitment on job satisfaction and emplooyes performance of PT. Bank Rakyat Indonesia (Persero) Tbk., Semarang Regional Office. The number of samples was 150 empployees and it was selected through proportional random sampling. SEM-PLS was applied to analyze the data. The conclusions indicated that organizational commitment directly influenced job satisfaction positively. Organizational commitment directly and positively influenced employees performance. Job satisfaction directly and positively influenced employees performance. To improve employees performance, the guidance for employees to be able to work in a team, increasing the sense of responsibility to the organization, giving employees the freedom to innovate, creating a comfortable working atmosphere and establishing good communication among employees with superior supervisor should be done